1984
DOI: 10.1007/bf00395485
|View full text |Cite
|
Sign up to set email alerts
|

The tumor-inhibiting effect of isomeric dichloro(diphenylethylenediamine)platinum(II) complexes

Abstract: Ring unsubstituted dichloro(diphenylethylenediamine)platinum(II) complexes show a dependence of their antitumor activity on the configuration and position of phenyl rings in ethylenediamine ligand. Dichloro(1,1-diphenylethylenediamine)platinum(II) (1d) and meso-dichloro(1,2-diphenylethylenediamine)-platinum(II) (meso-2d) have a weaker effect on the human breast-cancer cell line MDA-MB 231 and on rat leukemia L 5222 than (+/-)-dichloro(1,2-diphenylethylenediamine)platinum(II)((+)-2d) and its enantiomers (+)-2d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…25,26 Particularly, it has been reported that optically pure (1,2-diarylethane-1,2-diamine)dichloroplatinum(II) complexes induce significant inhibitory effects on the growth of leukemic and tumor cells, and a distinctly better effect was generally observed with the R,R/S,S configurations compared with the R,S counterparts. [27][28][29][30] These results motivated us to apply the findings from platinum(II) complexes to iridium(III) complexes. In this manuscript, we report the synthesis of novel dichlorobis[enantiopure 1,2-diarylethane-1,2-diamine]iridium(III) chlorides (general formula see Graphic Abstract) and their antiproliferative effects on a panel of representative human solid tumor cell lines.…”
Section: Introductionmentioning
confidence: 89%
“…25,26 Particularly, it has been reported that optically pure (1,2-diarylethane-1,2-diamine)dichloroplatinum(II) complexes induce significant inhibitory effects on the growth of leukemic and tumor cells, and a distinctly better effect was generally observed with the R,R/S,S configurations compared with the R,S counterparts. [27][28][29][30] These results motivated us to apply the findings from platinum(II) complexes to iridium(III) complexes. In this manuscript, we report the synthesis of novel dichlorobis[enantiopure 1,2-diarylethane-1,2-diamine]iridium(III) chlorides (general formula see Graphic Abstract) and their antiproliferative effects on a panel of representative human solid tumor cell lines.…”
Section: Introductionmentioning
confidence: 89%
“…The platinum(I1) complexes (as sulfates) diaqua(rneso-1,2-diphenylethylenediamine)platinum(II) [ [Pt(H20)2(rac-20H)]2+ were synthesized according to [4][5][6][12][13][14] and were gifts of Dr. Schonenberger (Regensburg, FRG). Cisplatin was a gift of Degussa (Frankfurt, FRG).…”
Section: Methodsmentioning
confidence: 99%
“…This drastic reduction method was unsuccessful for the 1,2-diaryl-1,2-diazidoethanes substituted in ortho and para position. By means of catalytic hydrogenation threo-l-(2-methoxyphenyl)-2-phenyl-1,2-ethanediamine (9) was obtained free of byproducts and in high yields (Scheme 1, method A).…”
Section: (3)mentioning
confidence: 99%